Mutagenic Impact Of Ethyl Methane Sulphonate On Morphological And Cytological Effects In Berseem (Trifolium Alexandrinum L.) (Applied Biological Research, 2023)
Induced mutagenesis has been effectively demonstrated as one of the best  possible methodology for the genetic improvement of crop species. Egyptian  clover (Trifolium alexandrinum L.), an important green fodder plant species of  the family Fabaceae with immense agricultural value, was selected for the  present study to improve its genetics by using the strategy of induced  mutagenesis. Dry and healthy seeds of Egyptian clover cv. ‘Wardan’ were  exposed to different doses (0.1, 0.3 and 0.5%) of Ethyl methane sulphonate  (EMS) for variable time (3 and 5 h). The germination and survival percentages  were recorded in M1 generation and 0.3% EMS at 5 h was determined as LD50  dose; whereas frequency of chlorophyll mutants and viable mutants along with  cytological observations were screened in M2 generation. A broad spectrum of  chlorophyll and viable mutants with different frequencies were observed.  Cytological abnormalities increased along with rising EMS concentrations and  mutagen exposure time. The findings are encouraging and show that significant  genetic variability had been induced by EMS. Thus, tcomprehensive selection of the desirable mutants may bring about advancement of improved and high  yielding mutants of T. alexandrinum in upcoming generation.
Keywords: Berseem; chlorophyll mutants; cytological abnormalities; ethyl methane sulphonate; mutagenesis; mutation breeding